Tracking enterovirus and poliovirus circulation in Parma: Environmental surveillance from 2019 to 2024 - Zoni, Roberta; Palandri, Lucia; Mezzetta, Sandra; Fontana, Stefano; Colucci, Maria Eugenia; Affanni, Paola; Bracchi, Mariateresa; Albertini, Roberto; Pasquarella, Cesira; Righi, Elena; Veronesi, Licia (Acta Biomedica Atenei Parmensis, 2025)
Background and aim: Environmental Surveillance (ES), which gained renewed interest during the COVID-19 pandemic due to its effectiveness in the early detection of viral spread, has long been recognised as a critical component of the Global Polio Eradication Initiative. This approach has historically played a fundamental role in the early identification of poliovirus transmission and remains an essential tool for monitoring the circulation of enteroviruses, underscoring its enduring significance in public health surveillance. This study aims to present six years ES data on poliovirus and enterovirus in Parma, Italy.Methods: The samples were collected every two weeks at the inlet of two sewage treatment plants and underwent a WHO protocol analysis. We detailed the temporal and spatial distribution of non-polio enterovirus (NPEV) and poliovirus based on the virus cultures algorithm from 2019 to 2024.Results: A total of 228 sewage samples were collected, a median of 44 samples per year. 68.9% resulted in positive cell cultures, without significant differences among the two treatment plants. The year 2023 had the highest percentage of NPEV isolates (97.7%), followed by 2024 and 2022 (87% and 70.5% respectively). 2021 had the overall lowest positive (35.6%). One Sabin-like strain type 3 was detected in 2022. Seasonal time trends were observed.Conclusions: This study contributes to a better understanding of NPEV circulation patterns in a pandemic and post-pandemic period, underlining the importance of ES as a tool in the assessment of the epidemiological spreading of enteroviruses and significantly poliovirus.